Implementasi Pendidikan Agama Islam Melalui Metode Kepramukaan di Madrasah Aliyah Ma’arif NU Doplang - Karjo Karjo (AL-BURHAN, 2022)
The similarity between scouting values and the 2013 curriculum allows the application of both simultaneously, especially in Islamic education. The scouting method is an interactive and progressive way of learning that includes aspects of obeying the code of honor, learning by doing, group system, attracting and challenging, adult presence, open nature, and a sign system of skills relevant to Islamic religious education. The purpose of this study was to determine, analyze, and describe the application of scouting methods and scouting method strategies that were used as the implementation of Islamic religious education at MA Ma'arif NU Doplang. This research is a qualitative research postpotivism. The research subjects were students of class XI-IPS Madrasah Aliyah Ma'arif NU Doplang Blora Regency in the 2021/2022 academic year, totaling 23 students. The object of research includes the understanding and obedience of students in carrying out Islamic religious law according to the standardization in the scouting curriculum and the core competencies of spiritual attitudes in the 2013 curriculum in class XI. The data presented in this study uses observational data collection techniques that involve scout coaches and religious group subject teachers, direct observation, and observation of documents for achieving General Proficiency Requirements (SKU) as well as the syllabus for Fiqh and Akidah Akhlak subjects. The data obtained were analyzed using case study data analysis techniques. The agreement between the scout coaches and subject teachers has made the output of scouting activities recognized as the result of PAI field activities at MA Ma'arif NU Doplang.